2023
DOI: 10.1371/journal.pone.0275767
|View full text |Cite
|
Sign up to set email alerts
|

A national professional development program fills mentoring gaps for postdoctoral researchers

Abstract: The Postdoc Academy: Succeeding as a Postdoc was designed to build postdocs’ skills in career transition, career planning, collaborative research, resilience, and self-reflection. This study examined self-reported changes in five skills as learners progressed through the course. Data were collected from participants who responded to both pre- and post-surveys and engaged with the course learning activities. Results from repeated measures multivariate analysis of variance revealed that all of the self-reported … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Postdoc Academy is available as a Massive Open Online Course (MOOC) on the edX platform as well as a separate website ( www.postdocacademy.org ). It was developed broadly to meet the needs of postdoctoral researchers in all fields [ 23 ]. Postdoc Academy is structured in two online asynchronous courses: (1) Succeeding as a Postdoc and (2) Building Skills for a Successful Career.…”
Section: Discussionmentioning
confidence: 99%
“…The Postdoc Academy is available as a Massive Open Online Course (MOOC) on the edX platform as well as a separate website ( www.postdocacademy.org ). It was developed broadly to meet the needs of postdoctoral researchers in all fields [ 23 ]. Postdoc Academy is structured in two online asynchronous courses: (1) Succeeding as a Postdoc and (2) Building Skills for a Successful Career.…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring is a learned skill, developed through training, mutual discussions, practice and feedback ( Hokanson and Goldberg, 2018 ). Over the past decade, research mentor training has grown from an area of relative weakness ( Cole et al, 2016 ) to an area which has demonstrated more widespread implementation, changing both practice and perspectives ( Pfund et al, 2014 ; Gandhi et al, 2019 ; Hamer et al, 2019 ; Desai et al, 2021 ; Alidina et al, 2022 ; Sun, T., et al, 2023 ). Yet, mentorship in LMICs remains challenged by few training hubs and platforms, poor institutionalization, turnover and loss of expertise, and limited recognition and funding [ Hansoti et al, 2019 ; Oppong et al, 2021 ; Health research mentorship in low and middle-income countries (HERMES), 2022 ].…”
Section: Introduction: Background and Rationale For The Educational A...mentioning
confidence: 99%